2017
DOI: 10.1002/cncr.30829
|View full text |Cite|
|
Sign up to set email alerts
|

Global and targeted serum metabolic profiling of colorectal cancer progression

Abstract: Background Patients with colorectal adenoma polyps (PLP) are at higher risk of developing colorectal cancer (CRC). However, the development of improved and robust biomarkers to enable screening, surveillance and early detection of PLP and CRC continues to be a challenge. The aim of this study was to identify biomarkers of progression to CRC by metabolomic profiling of human serum samples using a multistage approach. Methods Metabolomic profiling was conducted using Metabolon platform for 30 PLP, 30 CRC and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 33 publications
5
57
2
Order By: Relevance
“…Hypoxanthine has been previously reported to be increased in tumor tissue of colorectal cancer patients compared to normal tissue of healthy individuals. 15 In contrast, a recent study, 20 Like taurine, 5 hypoxanthine is an antioxidant and increased levels reported in our study may be the result of increased oxidative stress, 28 which is recognized as an important process in carcinogenesis, including colorectal cancer. 29,30 Inconsistent findings in hypoxanthine levels may be due to the type of specimen analyzed, or lack of statistical power because of lower sample numbers included.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Hypoxanthine has been previously reported to be increased in tumor tissue of colorectal cancer patients compared to normal tissue of healthy individuals. 15 In contrast, a recent study, 20 Like taurine, 5 hypoxanthine is an antioxidant and increased levels reported in our study may be the result of increased oxidative stress, 28 which is recognized as an important process in carcinogenesis, including colorectal cancer. 29,30 Inconsistent findings in hypoxanthine levels may be due to the type of specimen analyzed, or lack of statistical power because of lower sample numbers included.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast, a recent study, published by Long et al . reported decreased levels of hypoxanthine in colorectal cancer and polyps compared to controls . Like taurine, hypoxanthine is an antioxidant and increased levels reported in our study may be the result of increased oxidative stress, which is recognized as an important process in carcinogenesis, including colorectal cancer .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This feature arises from purine degradation that is usually observed in the SERS spectra of incubated blood samples . Interestingly, the level of hypoxanthine in SERS spectrum was reduced in CRC samples when compared with healthy control, which is consistent with the result of metabolomic profiling . The thymine signal at 741 cm −1 is also found to be generally stronger in the healthy group .…”
Section: Resultsmentioning
confidence: 99%